Dynamic Capabilities, Digital Transformation, and Sustainable Performance in Culinary SMEs: The Moderating Role of Customer Pressure in Samarinda - Dita Ananda; Wira Bharata (Bina Nusantara University, 2026)
This study investigates the role of dynamic capabilities —sensing, seizing, and reconfiguring in driving digital transformation and its impact on sustainable performance, while incorporating customer pressure as a moderating variable. Using a quantitative approach and the PLS-SEM method, data were collected from 312 respondents representing 13 culinary brands in Samarinda that have adopted the ESB application. The results indicate that dynamic capabilities significantly enhance digital transformation, which subsequently improves sustainable performance. Customer pressure is found to moderate the relationship between dynamic capabilities and digital transformation, exhibiting a unique moderation pattern: it weakens the influence of sensing and reconfiguring capabilities, yet strengthens the effect of seizing capabilities. This asymmetric moderating effect represents a novel contribution, as it reveals a shift in the direction of relationships not commonly reported in previous studies. Moreover, this research offers additional novelty by being the first to test an integrated model of dynamic capabilities, digital transformation, sustainable performance, and customer pressure specifically within ESB-enabled culinary businesses. Theoretically, the study enriches the existing literature by demonstrating how external, customer-driven pressures interact with organizational capabilities in the context of digital transformation. Practically, the findings provide strategic insights for culinary businesses seeking to optimize their digitalization efforts, manage customer expectations, and enhance long-term sustainability outcomes.